MOTIVASI JERMAN MENERIMA PENGUNGSI ASAL TIMUR TENGAH TAHUN 2015 - ", Zairani; ", Pazli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This Research is a contemporer study which analyzes about motivation of Germany to accepting many refugees from middle East, especially Syiria. Refugees is an issue that has existed since the world war ended. After War, World experienced many losses, not only the material and environment, but also make their population move to other country as refugees.Researcher analyzed this case using qualitative methods to find data and facts through some literature. The literature collected from books, journals, mass media and websites. Researcher use English School perspective which believe that country is main actor,this mazhab divided three pilars. The level analysis of the research is international system and also use foreign politic theory by Walter Carlsnaes.From this research it can be seen, Germany acccepting refugees because it has demography problen and needs a productive labour.Keywords: Motivation, Refugees, Demographics, labor